(untitled) (Journal of Gender and Social Issues, 2020)
The present study aims at focusing on what kind of beliefs are associated with the shrine visits that make them visitors believe and behave in a specific way. The shrine selected for this purpose was Bibi Pak Daman, Lahore, Pakistan. The visitors of this shrine were observed using nonparticipant observation method. Field notes were used to record observations and the data were analyzed using thematic analysis. Three major themes emerged out of the data. The first major theme of immortality appeared with sub-themes of belief in existence after death, belief in supernatural powers of chaste ladies and objects placed at the shrine. The second theme that emerged consisted of superstitions with the sub-themes of superstitions related to objects and miracles/mannat system. The third theme that emerged was of the beliefs in the light of the placebo effect and the sub-themes included prayer fulfillment, enhanced spirituality and problem resolution.